Concept Of Quality Development Of Primary Education In Uzbekistan - Jabborova Onakhon Mannapovna (Euro Asian Journal Publishing, 2023)
The article analyzes the main directions of the concept of qualitative development of primary education in Uzbekistan and presents individual approaches of the author
Keywords: Primary; skills; concept